Nebular phase observations of the Type-Ib supernova iPTF13bvn favour a binary progenitor - Kuncarayakti, H. (2015)
Aims. We present and analyse late-time observations of the Type-Ib supernova with possible pre-supernova progenitor detection, iPTF13bvn, which were done ~300 days after the explosion. We discuss them in the context of constraints on the supernova's progenitor. Previous studies have proposed two possible natures for the progenitor of the supernova, i.e. a massive Wolf-Rayet star or a lower-mass star in a close binary system. Methods. Our observations show that the supernova has entered the nebular phase, with the spectrum dominated by Mg I]λλ4571, [O I]λλ6300, 6364, and [Ca II]λλ7291, 7324 emission lines. We measured the emission line fluxes to estimate the core oxygen mass and compared the [O I]/[Ca II] line ratio with other supernovae. Results.The core oxygen mass of the supernova progenitor was estimated to be ≲0.7 M⊙, which implies initial progenitor mass that does not exceed ~15-17 M⊙.Since the derived mass is too low for a single star to become a Wolf-Rayet star, this result lends more support to the binary nature of the progenitor star of iPTF13bvn. The comparison of [O I]/[Ca II] line ratio with other supernovae also shows that iPTF13bvn appears to be in close association with the lower mass progenitors of stripped-envelope and Type-II supernovae. © 2015 ESO.